Functional roles of ADP-ribosylation writers, readers and erasers - Li, Ping; Lei, Yushuang; Qi, Jia; Liu, Wanqin; Yao, Kai (Frontiers in Cell and Developmental Biology, 2022)
ADP-ribosylation is a reversible post-translational modification (PTM) tightly regulated by the dynamic interplay between its writers, readers and erasers. As an intricate and versatile PTM, ADP-ribosylation plays critical roles in various physiological and pathological processes. In this review, we discuss the major players involved in the ADP-ribosylation cycle, which may facilitate the investigation of the ADP-ribosylation function and contribute to the understanding and treatment of ADP-ribosylation associated disease.